2012
DOI: 10.2135/cropsci2011.02.0082
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Resistance to Acetyl‐Coenzyme A Carboxylase‐Inhibiting Herbicides in Grain Sorghum

Abstract: Weed management is one of the most important considerations impacting sorghum [Sorghum bicolor (L.) Moench] production in the United States today. The objectives of this study were to evaluate the level of resistance, type of inheritance, and causal mutation of wild sorghum accessions that are resistant to acetyl-coenzyme A carboxylase (ACCase)-inhibiting herbicides compared to susceptible grain sorghum seed parents. Acetyl-coenzyme A carboxylaseinhibiting herbicides used in this study were fluazifop-P and qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Similarly, total irrigation amounts for sunflower beyond 254 mm were not profitable and the benefit of applying beyond 127 mm of irrigation water to sunflower was less than for corn and soybean. Although relative profitability will change with changes in input costs and grain prices, the greater economic profitability of corn and soybean with greater irrigation over sorghum or sunflower is in agreement with reports by Lamm et al (2007), Klocke et al (2014), and Taylor and Brix (2013).…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, total irrigation amounts for sunflower beyond 254 mm were not profitable and the benefit of applying beyond 127 mm of irrigation water to sunflower was less than for corn and soybean. Although relative profitability will change with changes in input costs and grain prices, the greater economic profitability of corn and soybean with greater irrigation over sorghum or sunflower is in agreement with reports by Lamm et al (2007), Klocke et al (2014), and Taylor and Brix (2013).…”
Section: Discussionsupporting
confidence: 83%
“…These included the W2027C mutation which was detected in Alopecurus myosuroides [16] Avena sterilis [32], Lolium [28], Phalaris minor [33] and Sorghum bicolor [34]. In black-grass the W2027C mutation was found to confer resistance to the FOP herbicides clodinafop-propargyl, haloxyfop-P-methyl and fenoxaprop-P-ethyl but not to the DIM herbicides cycloxydim and clethodim [35].…”
Section: Discussionmentioning
confidence: 99%
“…Target‐site resistance is essentially caused by single amino acid changes in the carboxyltransferase domain impacting on the effective binding of ACCase herbicides . It is therefore not surprising that some earlier studies have shown that target‐site resistance is more or less inherited as a monogenic trait . Exceptions to this rule are threefold increases in ACCase‐specific activity in two resistant S. halepense and Leptochloa chinensis populations from the United States and Thailand respectively .…”
Section: Mechanism Of Resistancementioning
confidence: 99%